Analysis on the Diffraction Characteristics of LCOS Dynamic Phase Grating - LI Wen-qing; WAN Zhu-jun; WAN Qiong (Guangtongxin yanjiu, 2016)
The electrical fringing field effect between neighboring pixels of the LCOS chip will result in a parasitic grating and the crosstalk among the ports of the WSS（Wavelength Selective Switch）module.A simplified 2foptical model was established and the relationship between the electrical fringing field effect and the performances of the WSS module was analyzed based on Fourier optics.The result shows that,with the increase of the diffraction angle of the LCOS grating,the crosstalk among the outputs of the WSS module increase.Reducing the space between the outputs or increasing the focal length of the lens can reduce the crosstalk,resulting in the more the number of outputs in the WSS module.The results presented in this paper are important for the parameter design and optimization of WSS module.